METHOD OF SETTING THE RULES OF MATRIX CONFIGURATIONS ELEMENTS INDEXING - I. P. Kadiev1; P. A. Kadiev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Aim. Develop a way to define the rules of indexing elements of combinatorial matrix configurations.Methods. Introduced are the proposed rules use examples during elements permutation of matrix combinatorial configurations defined are families of derived configurations, formed by the individual elements, provided the element location in each possible positions of the configuration, determined is the number of possible configurations forming variants with the specified index environment, forming separate families.Results. This article provides a method of setting the rules combinatorial matrix configurations elements indexing in the form of functional indices dependencies of environment elements of an element in the configuration from element indices, considered as a «central». A general view of the functional dependence of the index of elements surrounding the indices of any configuration item, regarded as a «central» is presented. The concept of elements «index remoteness» and the index remoteness coefficient, defined are the limits of its values.Conclusion. Permutations a predetermined environment indexing element may be considered as basic combinatorial configuration with which the reading of data by various algorithms can be arranged: in rows, in columns, in a deterministic or random routes that provides an additional increase in resistance disclosure.